Perbedaan Edukasi Melalui Instagram Dan Blog Terhadap Pengetahuan, Sikap, Dan Praktik Gizi Seimbang Mahasiswa Non-Kesehatan - Ainun Diyah Permatasari; Teguh Jati Prasetyo; Pramesthi Widya Hapsari (Journal of Applied Science for Pharmaceuticals and Health, 2025)
Background: Nutrition education is an intervention that could improve and increase nutrition knowledge. Nutrition knowledge will influence the attitude and practice in daily life. The example of social media based education are instagram and blogs. The study aims to examine the difference of nutrition knowledge, attitude and practice among Non-Health Science Students at Universitas Jenderal Soedirman about balanced nutrition education using instagram and blog. Methods: The design was quasi-experimental with pre and post-test group design. Twenty six student were taken use purposive sampling wich divided into 2 group. The intervention was conducted in 18 days. Knowledge, attitudes and practices was measured using questionnaire. Data was analysis used Wilcoxon and Mann-Whitney test. Results: The average increase in the instagram group's knowledge score was 11 to 17,46 (p=0,001), attitude was 48,92 to 53,62 (p=0,001), and practice was 71 to 74,46 (p=0.036). Meanwhile, the score for blog knowledge was 11,77 to 17,31 (p=0.001), attitude was 47 to 52,69 (p=0,001), and practice was 68,31 to 73,46 (p=0,030). There was no significant difference regarding knowledge (p=0,841), attitude (p=0,424) and practice (p=0,258) after nutrition education between giving by instagram and blogs. Conclusion: There were differences in knowledge, attitudes and practice before and after education. There were no differences in knowledge, attitudes and practices between education through instagram and blogs.